ER-associated mitochondrial division links the distribution of mitochondria and mitochondrial DNA in yeast - Andrew Murley; Laura L Lackner; Christof Osman; Matthew West; Gia K Voeltz; Peter Walter; Jodi Nunnari (eLife, 2013)
Mitochondrial division is important for mitochondrial distribution and function. Recent data have demonstrated that ER–mitochondria contacts mark mitochondrial division sites, but the molecular basis and functions of these contacts are not understood. Here we show that in yeast, the ER–mitochondria tethering complex, ERMES, and the highly conserved Miro GTPase, Gem1, are spatially and functionally linked to ER-associated mitochondrial division. Gem1 acts as a negative regulator of ER–mitochondria contacts, an activity required for the spatial resolution and distribution of newly generated mitochondrial tips following division. Previous data have demonstrated that ERMES localizes with a subset of actively replicating mitochondrial nucleoids. We show that mitochondrial division is spatially linked to nucleoids and that a majority of these nucleoids segregate prior to division, resulting in their distribution into newly generated tips in the mitochondrial network. Thus, we postulate that ER-associated division serves to link the distribution of mitochondria and mitochondrial nucleoids in cells.